Impacto do trabalho em profissionais de Saúde Mental de serviços de saúde do município de Mossoró-RN, 2012 - Moura, Glaudênia Alves de (2012)
The Psychiatric Reform has brought profound changes in assistance to people affected by mental disorders and behavior. In this context, mental health workers have played decisive roles of great impact, acting driving the process. Objective: To evaluate the impact felt by working professionals, because of the daily work with people who have psychiatric disorders. Methodology: This is a search field, a quantitative approach, sectional, descriptive and applied. Data collection occurred through the Assessment Scale Impact of Working in Mental Health Services (IMPACT-BR) applied to mental health researchers city Mossoró - RN. Results: Participants in this study 87 professionals, mostly female married, which took charge of higher education, working on a single service, working in the area for more than six years, aged between 25 and 64 years. There were a low effect of overloading the professionals surveyed. Discussion: Our results corroborate findings in other surveys conducted previously, not identifying large impact load at work among professionals of mental health teams studied. Subscales studied the highest score was observed in measuring the impact of work on team functioning. It was observed that the greater age and duration of action, reduced the emotional impact at work, suggesting that the experience enhances safety in decisions made and the possibility of greater control over the demands of work. Final Thoughts: The work presented showed that the interactive relationships between professionals and users are not the causes of greatest impact in the workplace, although it revealed overload in relation to specific aspects such as: fear of being assaulted by a patient and the feeling of physical exhaustion the end of the workday. Further investigations should be conducted on this topic in order to contribute to the implementation of psychiatric reform proposed by advances both in terms of assistance to individuals and the quality of life in the work of the professionals involved